THE IMPACT OF EXCESSIVE GADGET USE ON ADOLESCENT BEHAVIOR IN AL-HIDAYAH DORM - E Rizky Wulandari; Muhammad Habib Alfan (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
The development of information technology brings a change in society. The presence of gadgets, especially in the form of smartphones, has contributed a lot in everyday life, as a medium for seeking information, interacting, getting entertainment, and even doing business activities are also included in it. This journal aims to find out how the influence of gadgets on adolescent behavior in the Al-Hidayah dorm environment. This research is based on changes in adolescent behavior due to excessive use of gadgets. This research uses a qualitative approach with descriptive methods. The data was obtained through observing several residents of the Al-Hidayah dorm who used gadgets excessively. Data analysis was carried out from the beginning of this assignment until the assignment was collected.